2022
DOI: 10.1088/1758-5090/ac48e6
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cell migration on straight, wavy, loop and grid microfibre patterns

Abstract: Cell migration plays an important role in physiological and pathological processes where the fibrillar morphology of extracellular matrices (ECM) could regulate the migration dynamics. To mimic the morphological characteristics of fibrillar matrix structures, low-voltage continuous electrospinning was adapted to construct straight, wavy, looped and gridded fibre patterns made of polystyrene (of fibre diameter ca. 3 μm). Cells were free to explore their different shapes in response to the directly-adhered fibre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 70 publications
(94 reference statements)
0
10
0
Order By: Relevance
“…Cell–material interactions are critical for tissue regeneration. Cells respond to various material cues, cell cues and soluble factors. As material cues are concerned, surface topography and matrix stiffness are two physical factors which always exist more or less. The present study distinguishes itself as the focus understanding of a part of topological effect in light of overall stiffness effect.…”
Section: Discussionmentioning
confidence: 99%
“…Cell–material interactions are critical for tissue regeneration. Cells respond to various material cues, cell cues and soluble factors. As material cues are concerned, surface topography and matrix stiffness are two physical factors which always exist more or less. The present study distinguishes itself as the focus understanding of a part of topological effect in light of overall stiffness effect.…”
Section: Discussionmentioning
confidence: 99%
“…Nanofibers are extensively explored for cancer treatment because they can sustain the release of anti‐tumor drugs with specificity, integrated proliferation, angiogenesis and invasion and manipulation with the cancer cell migration 28 …”
Section: Biomedical Applications Of Nanofibersmentioning
confidence: 99%
“…The cells could take up the desired shapes as they adhered and migrated. The observation was primarily observed that while cells dynamically adjust their forms and relocation paths in response to various microfibrils' surroundings, the global fiber pattern has only a limited influence on their typical move speed; Secondarily, whenever the design characteristics approach the upper bound of the cell body's minor axis, a behavior change was observed, indicating that cells' potential to redirect from an existing fiber track is constrained by the dimensions along the cell body's minor axis 28 . Figure 5 illustrates the nanofiber application in cancer research and diagnosis.…”
Section: Biomedical Applications Of Nanofibersmentioning
confidence: 99%
“…With various planar fiber patterns, the role of morphological cues provided by ECM could be used to study cell migrations. Cancer cell migration dynamics were observed using LEP produced fibers of different patterns, and it was found that the upper limit of the cell body minor axis determined cells’ fiber switching ability, revealing fiber displacement as a key factor to consider in scaffold design (Figure b) . Suspended ECM protein-based fiber arrays were fabricated in situ on polymer frames, creating various patterns with a defined 3D structure.…”
Section: Versatile Fiber Scaffolds For Cell and Tissue Mechanics Studymentioning
confidence: 99%
“…Cancer cell migration dynamics were observed using LEP produced fibers of different patterns, and it was found that the upper limit of the cell body minor axis determined cells' fiber switching ability, revealing fiber displacement as a key factor to consider in scaffold design (Figure 6b). 52 Suspended ECM protein-based fiber arrays were fabricated in situ on polymer frames, creating various patterns with a defined 3D structure. The biocompatibility of 3D ECMbased fiber array was demonstrated by culturing glioblastoma cells (Figure 6c).…”
Section: Versatile Fiber Scaffolds For Cell and Tissue Mechanics Studymentioning
confidence: 99%